BANALITAS SIMBOL KEAGAMAAN DALAM SINETRON RELIGI: Analisis Tayangan Sinetron “Bukan Islam KTP” di SCTV - Siti Solikhati; Heddy Shri Ahimsa Putra; Heru Nugroho (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2015)
The banality of religious symbols used in television soap opera has caused the distortion on meaning, so that some values of religious teachings have moved away from its substance. By observing the religious soap opera entitled “Bukan Islam KTP”, the writer tries to find out how such banality happens. This piece of work finds out that, in this soap opera, verbal and non-verbal religious symbols have been constructed in such a way for the sake of market interest as well as for the benefits of the symbol creator. This aim is carried out by representing religious teaching using entertainment program.***Banalitas penggunaan simbol-simbol keagamaan dalam tayangan sinetron di televisi telah mengakibatkan pembelokan makna, sehingga ajaran agama telah bergeser dari substansinya. Tulisan ini bermaksud untuk menemukan bagaimana peristiwa banalitas tersebut terjadi, dengan meneliti tayangan sinetron religi “Bukan Islam KTP”. Dalam sinetron ini, simbol kegamaan yang bersifat verbal dan non-verbal dikonstruksikan sedemikian rupa untuk kepentingan pasar serta keuntungan produsen pesan, dengan menyajikan program keagamaan yang bersifat hiburan.